Religious Norms vs. Global Trade Regulations: An Analysis of the WTO DS477/478 Dispute and Indonesia’s Halal Certification - Sutrisno, Andri; Priyono, F.X. Joko; Trihastuti, Nanik; Maulidah, Khilmatin; Wendra, Muhammad (Universitas Internasional Batam, 2025)
This study examines Indonesia’s halal certification as both a legal instrument and an economic policy with direct implications for international trade. Using a normative juridical approach combined with qualitative economic analysis, it explores Law No. 33 of 2014 on Halal Product Assurance (UUJPH) and its application to meat import policies, particularly in the aftermath of WTO disputes DS477/478. Halal certification is framed as a fundamental necessity for Indonesia’s Muslim majority and as a legitimate objective under Article XX(a) of the GATT 1994, which protects public morals. The findings highlight two strategic dimensions of the policy: first, consumer protection and the enforcement of maqāṣid al-sharīʿah through traceable ingredients and production processes; second, its role as an economic tool to enhance product competitiveness, expand international market access, and strengthen Indonesia’s position within the global halal supply chain. However, significant challenges persist. Domestically, limited legal literacy, certification costs, and the constrained capacity of micro, small, and medium enterprises (MSMEs) hinder certification uptake. Internationally, mandatory halal certification is sometimes perceived as an additional technical barrier to trade, sparking trade disputes. Analysis of GATT 1994 Articles III and XI and TBT Agreement Articles 2.2 and 2.4 underscores the need for Indonesia’s policy to avoid unjustifiable discrimination and unnecessary trade restrictions. The study concludes that harmonizing the protection of public morals with multilateral trade commitments is essential. Policy recommendations include revising the UUJPH to align with international standards, strengthening the Halal Product Assurance Agency’s capacity, providing incentives and support for MSMEs, and expanding mutual recognition agreements with key trading partners. With evidence-based, transparent, and inclusive policies, Indonesia can reinforce its role as a global halal industry hub while safeguarding its trade reputation and balancing religious values with international trade obligations.